microRNA 146a ameliorates retinal damage in experimental autoimmune uveitis - Sindhu Saraswathy; Narsing A. Rao (Frontiers in Ophthalmology, 2023)
IntroductionUveitis and related intraocular inflammations are a major cause of blindness due to retinal damage caused by degeneration and loss of the photoreceptor cells. In mouse experimental autoimmune uveitis (EAU) previously we have shown mitochondrial oxidative stress with marked upregulation of αA crystallin in the inner segments of the photoreceptors. Furthermore, αA crystallin treatment prevented photoreceptor mitochondrial oxidative stress by suppressing innate and adaptive immunity in EAU.MethodsSince these immune processes are modulated by microRNAs, in this study we investigated (a) modulation of microRNAs during development of EAU by αA crystallin administration and (b) microRNA therapeutic intervention.ResultsFew microRNAs were significantly upregulated in EAU mice with intravenous injection of αA crystallin and among these, computational bioinformatic analysis revealed that the upregulated microRNA 146a targets the innate and adaptive immune responses. In EAU, intravenous as well as intravitreal administration of this microRNA prevented inflammatory cell infiltration in uvea and retina and preserved photoreceptor cells.DiscussionThis protective function suggests that microRNA146a can be a novel therapeutic agent in preventing retinal damage in uveitis.